Evaluation of agreement of IOP measurements by Tono-Vera tonometer to Goldmann applanation tonometry - Niles, Charles R.; Crinzi, Alexander R.; Bonaventura, Russell; Taylor, David A. (Frontiers in Ophthalmology, 2024)
PurposeTo evaluate the accuracy of the new Tono-Vera rebound tonometer (Reichert Inc, Buffalo, NY) compared to Goldmann Applanation Tonometry.MethodsThis prospective, observational, cross-sectional study was designed in accordance with ANSI Z80.10-2014 and ISO 8612-2009 guidelines for tonometer comparison. Intraocular Pressure (IOP) was measured by Goldmann Applanation and Tono-Vera on 160 eyes of 160 subjects. Corneal Astigmatism and Central Corneal Thickness were also measured. A single investigator (CN) conducted all measurements. The average of two measurements from each tonometer was used in the analysis. Bland-Altman plots, total least squares regression analysis, and simple linear regression were used to evaluate agreement between the tonometers.ResultsAverage IOP values from Goldmann Applanation and Tono-Vera were not significantly different (19.17 and 19.03 respectively, p=0.40, paired t-test). The total least squares regression analysis indicated strong agreement between the two tonometers (slope +0.97, offset +0.49 mmHg, standard deviation 2.11 mmHg). There were 2 IOP measurement pairs that exceeded the ± 5 mmHg limits of agreement required in ANSI Z80.10-2014 and ISO 8612-2009, which is within the range of acceptability specified in the standards.ConclusionWe evaluated IOP measurements by Tono-Vera Rebound Tonometer vs Goldmann Applanation Tonometry for eyes with a wide range of IOP values and found no statistically significant differences in the results. Tono-Vera meets the requirements of ANSI Z80.10-2014 and ISO 8612-2009, demonstrating accuracy comparable to Goldmann tonometry.